2014
DOI: 10.5603/ep.2014.0001
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulina, adiponektyna i hsCRP u kobiet w wieku rozrodczym z zespołem policystycznych jajników (PCOS) — wpływ leczenia metforminą

Abstract: Introduction: Women with polycystic ovary syndrome (PCOS) often suffer from obesity and insulin resistance. The role of proinsulin, which is known to be an indicator of fertility outcomes in PCOS women, and that of adiponectin, in the pathogenesis of PCOS is not well elucidated. Our objective was to determine proinsulin, adiponectin, hsCRP and other hormonal and metabolic parameters in PCOS women before and after metformin treatment. Material and methods: Two PCOS groups of patients of reproductive age (90 lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
4
1
Order By: Relevance
“…Increased adiponectin levels observed in patients with PCOS after metformin administration may be the result of reduced insulin resistance and insulin levels. However, inconsistent with our results, the results of another study [ 31 ] indicated no change in adiponectin concentration after treatment with 1000 mg of metformin daily for 6 months. These conflicting results could be explained by the relatively small sample size and difference in study populations, including differences in race, BMI, and severity of insulin resistance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Increased adiponectin levels observed in patients with PCOS after metformin administration may be the result of reduced insulin resistance and insulin levels. However, inconsistent with our results, the results of another study [ 31 ] indicated no change in adiponectin concentration after treatment with 1000 mg of metformin daily for 6 months. These conflicting results could be explained by the relatively small sample size and difference in study populations, including differences in race, BMI, and severity of insulin resistance.…”
Section: Discussioncontrasting
confidence: 99%
“…Seven studies, including 280 women, were eligible for the meta-analysis [ 27 29 , 31 , 32 , 42 , 43 ]. The I 2 value was 69%, indicating moderate heterogeneity among the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that insulin resistance may have a pivotal role in the development of PCOS; nonetheless, the pathophysiology of this disease has not been wholly elucidated [4]. This syndrome is associated with a higher incidence of sub-clinical chronic inflammation, obesity, and related disorders including insulin resistance, metabolic syndrome, diabetes mellitus, hyperlipidaemia, and cardiovascular risk [2,[5][6]. Hyperinsulinaemia and decreasing insulin sensitivity usually contribute to metabolic disturbances in PCOS [2].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, women who are able to maintain normal weight with aging appear to boast a healthier metabolic profile than those who do not [ 62 ]. These differences may influence the impact of metformin in each group [ 63 ]: whereas reproductive benefits are observed in both obese and lean PCOS women [ 64 ], metabolic advantages, such as lowering of proinsulin and insulin levels, are seen predominantly in the obese and overweight subset [ 65 ].…”
Section: Insulin Resistance As the Key Endocrine Disruption In Polmentioning
confidence: 99%